[The scientific collaboration on a hydrogeological mapping project between the Geological Survey of Italy (ISPRA) and the China Geological Survey] - Gafà, Rossella Maria; La Vigna, Francesco; Martarelli, Lucio; Monti, Gennaro Maria; Silvi, Angelantonio (Acque Sotterranee - Italian Journal of Groundwater, 2021)
Not available